Cultural Adaptation of 2 Evidence-Based Alcohol Interventions for Antiretroviral Treatment Clinic Patients in Vietnam. (10th June 2019) - Hutton, Heidi Elizabeth; Lancaster, Kathryn Elizabeth; Zuskov, Diana; Mai, Nguyen Vu Tuyet; Quynh, Bui Xuan; Chander, Geetanjali; Latkin, Carl Asher; The Vu, Pham; Sripaipan, Teerada; Ha, Tran Viet; Go, Vivian Fei-Ling
In Vietnam where alcohol use is culturally normative and little treatment is available, persons living with HIV (PLWH) who consume alcohol at unhealthy levels are at greatly increased risk for negative health outcomes. We describe the first systematic adaptation of 2 evidence-based alcohol interventions for use in Vietnam: a combined motivational enhancement therapy/cognitive behavioral therapy and a brief alcohol intervention. Using the situated information, motivation and behavioral skills model, and systematic procedures for tailoring evidence-based treatments, we identified core intervention content to be preserved and key characteristics to be tailored for relevance to the clinical setting. We describe the use of in-depth interviews with antiretroviral treatment clients and providers, expert input, and counselor training procedures to develop tailored manuals for counselors and clients. Adapting evidence-based alcohol treatments for global settings is facilitated by the use of a model of behavior change and systematic procedures to operationalize the approach.